Estudio de factibilidad para una empresa productora y comercializadora de bebidas refrescantes carbonatadas, endulzadas a base de panela, en la ciudad de Bogotá, D.C. (2017)
The feasibility study for the creation of a company producing and marketing carbonated soft drinks based with panela in the Bogotá, DC city. Began with a diagnosis of the environment, where the sector and subsector of manufacturing and of beverages in the country and in Bogotá, DC, it was determined that the industry although it comes in a state of low growth, the beverage subsector is one of the most contributes to the PIB of the sector. The market study was established as niche restaurants in Usaquén and Chapinero. The Nattiva name was chose. The technical study, the capacity of 303 soda per day, a single operator and a working day were determined. It continued with the realization of the administrative study, where the organizational structure was made and Colombia Refrescante S.A.S was imposed as social reason for the benefits that this type of constitution. The entire financial study was developed, consolidating all costs and expenses in an income statement and generating a cash flow, Using financial indicators to establish the feasibility and viability of the project.